Cancer-Related Fatigue and Its Associations with Depression and Anxiety: A Systematic Review - Brown, Linda F. (2009)
BACKGROUND: Fatigue is an important symptom in cancer and has been shown to be associated with psychological distress. OBJECTIVES: This review assesses evidence regarding associations of CRF with depression and anxiety. METHODS: Database searches yielded 59 studies reporting correlation coefficients or odds ratios. RESULTS: Combined sample size was 12,103. Average correlation of fatigue with depression, weighted by sample size, was 0.56 and for anxiety, 0.46. Thirty-one instruments were used to assess fatigue, suggesting a lack of consensus on measurement. CONCLUSION: This review confirms the association of fatigue with depression and anxiety. Directionality needs to be better delineated in longitudinal studies.